2022
DOI: 10.1155/2022/2970229
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated Development of Artificial Intelligence and Economic Management

Abstract: The world economy is developing rapidly. Behind the rapid development, the management of economic regions is very important. In the process of economic management, the government plays the role of macrocontrol and is responsible for the management of various economic affairs and social and economic services. While undertaking infrastructure construction, it creates a good environment for economic development. However, with the deepening of economic development and the more and more complex economic data, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Economic spheres have expanded further, which has made it difficult to manage regional and national economies. Thus, since economic management plays an important role in economic development, it greatly affects the correctness of economic development [18].…”
Section: Relevance and Setting Of The Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic spheres have expanded further, which has made it difficult to manage regional and national economies. Thus, since economic management plays an important role in economic development, it greatly affects the correctness of economic development [18].…”
Section: Relevance and Setting Of The Problemmentioning
confidence: 99%
“…As economic development continues, people's living standards will also improve. In order to ensure the efficient operation of economic development, many scientists and researchers have conducted many studies on the application of digital technologies in the operation of economic development [1,2,3,5,11,18].…”
Section: Relevance and Setting Of The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%